Pengembagan Bahan Ajar Fisika Berbentuk E-Modul Berbasis Kontekstual Menggunakan Aplikasi eXe-Learning Pada Materi Usaha dan Energi - Kiki Andila Andila; Hadma Yuliani; Nur Inayah Syar (Universitas Hamzanwadi, 2021)
This research aims to determine: 1) the procedure for teaching materials in the form of e-modules 2) the feasibility of teaching materials in the form of e-modules 3) the responses of students to the e-modules developed. This study uses the ADDIE Model Research and Development (R&D) method. The stages are needs analysis, design, development, implementation and evaluation. The results of this study are: 1) the procedure for making teaching materials in the form of e-modules, namely analysis, design of teaching materials by determining the format of teaching materials, development, namely the validation of teaching material products through validation of media experts, materials and learning, implementation to students through small group tests. 2) the feasibility of teaching materials in the form of e-module, the results of the media expert's assessment obtained a percentage of 75% with good and feasible criteria. The results of the material expert's assessment obtained a percentage of 76.2% with good and feasible criteria. The results of the learning expert's assessment obtained a percentage of 82% with good criteria and suitable for use. 3) The results of the students' responses obtained a percentage of 85% in the very good category.